Design of Speed-Controller for Brushless DC-Motor Based on Grey Predictor-PID Controller - Mohammed Ezzaldean (Engineering and Technology Journal, 2018)
Brushless direct current (BLDC) motor is a permanent-magnet synchronous motor but the commutator and the brushes are replaced by electronic commutation system. This motor is characterized by many advantages compared with other motors and it being used in a wide range of applications. In BLDC motor, speed control plays an essential role; the speed-controller has to respond rapidly to command changes and to offer enough robustness against the variations of the mechanical load. In this paper, the design of Grey-PID controller is proposed as speed controller of BLDC motor where a new adaptation algorithm is suggested to update the parameters of the adaptive PID controller. The proposed algorithm takes advantages of both of Grey model GM(1,1) and gradient-descent method. The Grey-PID speed control system is simulated by using Matlab\Simulink environment. The simulation results confirm that the proposed controller performs better than the traditional PID controller. By using Grey-PID controller, starting the motor or sudden change of speed can be performed with short rise and settling times, no overshoot and no steady-state error. The proposed controller, also, has a great ability to restrain the fluctuation of speed caused by load disturbance.